EFFECTIVENESS OF LOCAL ANAESTHETIC IN REDUCING POSTOPERATIVE PAIN AT PORT SITE AFTER LAPAROSCOPIC CHOLECYSTECTOMY - Bukhari, Saima; Akbar, Ismail; Shoaib, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Laparoscopy has become the highest quality level way to deal with cholecystectomy since its inception 30 years preceding, and is perhaps the most normally performed general surgeries. Pain being a significant issue after laparoscopic cholecystectomy bringing about extended admissions or readmissions. With significant varieties in pain relieving conventions an integrated approach is important to diminish pain. The aim of this study is to assess the effectiveness of Bupivacaine as local anesthetic agent at port sites after laparoscopic cholecystectomy. Methods: Study population of 84 patients was divided into control group (receiving no local anesthetic) and study group (receiving Bupivacaine as local anesthetic). Visual analogue scale was used to quantify and compare pain perceived by each group; at fixed intervals of 6, 12 and 24 hours after shifting of the patients back to the ward. Results: Each group comprised 42 patients. At 6 hours post operative pain score in study group, 4.5±0.32 was significantly lower than in control group, 7.6±0.41 (p<0.05). Though pain assessments at 12 and 24 hours didn’t reveal any significant differences among the two groups; postoperative requirement of Tramadol was significantly (p<0.05) lower in study group (92±0.064mg) in comparison to control group (158±0.21mg). Conclusion: Use of long-acting local anesthetic injections at port sites after laparoscopic cholecystectomy significantly lowers pain during first 6 hours post operatively and also lowers narcotic analgesics requirements during post operative period.